2004
DOI: 10.1038/sj.ejcn.1601943
|View full text |Cite
|
Sign up to set email alerts
|

High-dose intravenous vitamin C is not associated with an increase of pro-oxidative biomarkers

Abstract: Objective: High-dose vitamin C therapy might mediate beneficial clinical effects by counteracting reactive oxygen species. However, concerns are raised whether this approach might provoke diametrical (ie pro-oxidative) effects. The objective was to determine ascorbyl free radical (AFR) concentrations and potential variables of pro-oxidative damage. Design: Crossover study; six healthy males received daily infusions of 750 or 7500 mg vitamin C for six consecutive days. Fasting concentrations of vitamin C and AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 31 publications
2
26
0
1
Order By: Relevance
“…Repeated i.v. injection of 750-7500 mg/day of vitamin C for 6 days in healthy volunteers does not induce a pro-oxidant change in plasma markers (38). Further, i.v.…”
Section: Vitamin C Dosage and Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated i.v. injection of 750-7500 mg/day of vitamin C for 6 days in healthy volunteers does not induce a pro-oxidant change in plasma markers (38). Further, i.v.…”
Section: Vitamin C Dosage and Safetymentioning
confidence: 99%
“…However, concerns have been raised that highdose ascorbate may induce pro-oxidant effects in patients (38). One basis for this concern is that ascorbate reduces the valence of free transition metals, such as iron (e.g., ascorbate reduces FeIII to FeII), which then catalyze the formation of hydrogen peroxide.…”
Section: Vitamin C Dosage and Safetymentioning
confidence: 99%
“…The volunteers were instructed by a nutritionist to exclude from their diets foods rich in AA and iron (such as vegetables, legumes, fruit, juice, coffee, tea, egg and all types of meat) as well as foods containing phytates, tannins and calcium, among others, on the day before and during the blood sampling period. The time points were selected based on literature absorption curves for AA and iron [16,20,26,27] . The 24-hour time point was chosen with the intention of searching for a possible delayed prooxidative effect of vitamin C and Iron.…”
Section: Subjectsmentioning
confidence: 99%
“…AA is a powerful water-soluble antioxidant which can prevent peroxidation in plasma after exposure to a variety of prooxidative situations [14][15][16] . In line with this, AA deficiency is always associated with an increase in oxidative stress and tissue injury [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the simulation of the mathematical model, the increase of intracellular H2O2 due to IVA in humans should be limited and unlikely to induce cell death. Muhlhofer et al's study might provide some evidence for this, which showed that there was no increase in the plasma concentrations of α-tocopherol and thiobarbituric acid-reactive substances, a well-established parameter for lipid peroxidation, in six healthy males who received daily infusions of up to 7.5 grams ascorbate for six consecutive days [127], though the dose used was only around 1/10 of that was usually used in a IVA treatment for cancer [36].…”
Section: Discussionmentioning
confidence: 99%